Taking Stock of the English Word Stock: The Rise and Expansion of Covid-19-Inspired Terminology - Naumoska Sarakinska, Biljana (Fakultet za pravne i poslovne studije “Dr. Lazar Vrkatić”, 2022)
In just less than two years, the COVID-19 pandemic has managed to leave a mark on a number of areas of life and fields of study, and linguistics has not been exempted. As everyone deals with the ‘new normal’ brought about and shaped by the pandemic, we have had to rise to the challenge of deciding how to talk about the influence of the virus on our day-to-day lives. The constant changes that are occurring in medicine, politics, education, entertainment, among others, reflect the need for a greater use of already-existing lexemes, as well as new terminology that will help us make sense of those societal changes. The English vocabulary is a work in progress, and the lexeme formation processes that occur are intensified by our online presence during the months-long lockdowns, quarantines, and restrictions. People’s creativity during online communication has resulted in many new terms and phrases, some of which have already been noted in online dictionaries – from the Oxford University Press and the Cambridge University Press, to Macmillan and Merriam-Webster. The lexemes looked at in this paper have been taken from a variety of mainly online sources, however, not just from the said dictionaries. This paper will take a closer look at the meaning and function of these increasingly used lexemes, as well as the processes that have taken place in their creation, such as affixation (zoomwear), compounding (social bubble), clipping (isolation), blending (covidiot), and abbreviation (WFH – working from home).
Keywords: lexeme formation (processes), (derivational) neologisms, productivity